Re-evaluation of neuronal P2X7 expression using novel mouse models and a P2X7-specific nanobody - Kaczmarek-Hajek, Karina; Zhang, Jiong; Kopp, Robin; Grosche, Antje; Rissiek, Bjoern; Saul, Anika; Bruzzone, Santina; Engel, Tobias; Jooss, Tina; Krautloher, Anna; Schuster, Stefanie; Magnus, Tim; et al. (eLife, 2018)
The P2X7 channel is involved in the pathogenesis of various CNS diseases. An increasing number of studies suggest its presence in neurons where its putative functions remain controversial for more than a decade. To resolve this issue and to provide a model for analysis of P2X7 functions, we generated P2X7 BAC transgenic mice that allow visualization of functional EGFP-tagged P2X7 receptors in vivo. Extensive characterization of these mice revealed dominant P2X7-EGFP protein expression in microglia, Bergmann glia, and oligodendrocytes, but not in neurons. These findings were further validated by microglia- and oligodendrocyte-specific P2X7 deletion and a novel P2X7-specific nanobody. In addition to the first quantitative analysis of P2X7 protein expression in the CNS, we show potential consequences of its overexpression in ischemic retina and post-traumatic cerebral cortex grey matter. This novel mouse model overcomes previous limitations in P2X7 research and will help to determine its physiological roles and contribution to diseases.
EVALuna2:35806